Plant-based effervescent tablet for purification of contaminated water - Cabatac,Ernestine Angela M.
Many plants abundant in the Philippines have principles with biosorbent and antimicrobial properties. These chemicals are present even in plant parts that are unused and thrown as waste. In this study, plant-based effervescent tablets were formulated to purify water and remove potentially harmful contaminants. Four types of tablets combinations were created from two of these dried and powdered plant materials; rinds of Durian (Durio zibethinus Murr), Mangosteen (Garcinia mangostana Linn), peels of Suha (Citrus grandis Osbeck) and leaves of Bayabas (Psidium guajava Linn). Tablet parameters such as weight, hardness, thickness, disintegration time and taste imparted to water are determined. The tablet formulations were evaluated based on their lead and cadmium biosorption and antibacterial activitity. Considering both properties, the combination tablet of Durian and Bayabas (DuBay Tablets) had performed consistently well. It had a biosorption of 5.6867 mg Cd/g sorbent (49.44% Cd sorbed) and 12.9449mg Pg/g sorbent (72.77% PbSorbed). It also exhibited a remarkable activity against Escherichia coli, Staphylococcus aureus, and the microbial flora of Pasig River water. It was recommended though that crude aqueous extracts from the plant materials used may be added to increase bactericidal activity. DuBay Tablet's production and materials costs were also determined.